Prevalensi Kehamilan Berisiko dan Karakteristiknya pada Ibu Hamil di Puskesmas Sukamulya Periode Tahun 2020 - Edwin Perdana; Adrian Goenawan; Nadia Tasya Saputra (Jurnal MedScientiae, 2022)
Maternal Mortality Rate (MMR) is one of the important parameters to measure the degree of public health in a country. Pregnant women who have high risk pregnancy risk factors have a higher risk of morbidity and mortality than women with low-risk pregnancies. Objective for knowing the prevalence of risky pregnancies and their characteristics in pregnant women at the Sukamulya Public Health Center in 2020. This study uses total sampling method. There were 136 research subjects who met the inclusion criteria. Data is collected by secondary data in the form of medical records. The majority of the subjects were pregnant women with high-risk pregnancies (72.8%) with the risk factors possessed by pregnant women at the Sukamulya Public Health Center from the highest to the lowest, respectively, were comorbidities (52.9%), age (36.8%), BMI (19.1%), history of cesarean (17.6%), blood pressure (16.9%), total parity (8.8%), gestational interval (7.4%), history of habitual abortion (3.7%), number of fetuses (2.9%), and maternal height (1.5%). The majority of pregnant women at the Sukamulya Health Center, Cigugur Village, Kuningan, West Java are pregnant women with high risk pregnancies (72.8%).